Volatiles produced by bacteria in the honeydew of cotton aphids mediate prey location by Hippodamia variegata (Coleoptera: Coccinellidae) - Panjing Liu; Tao Zhang; Yu Gao; Xiaofang Zhang; Hongyi Wei; Yanhui Lu (Biological Control)
Honeydew produced by insects is not only recognized as a nutrient-rich substance for natural enemies, influencing their survival, development, and reproduction but also a source of volatiles that regulate the foraging behavior of natural enemies. Hippodamia variegata (Coleoptera: Coccinellidae) is an effective predatory natural enemy of Aphis gossypii (Hemiptera: Aphididae) in Xinjiang, China. However, the functional significance of honeydew volatiles from A. gossypii for H. variegata remains largely unclear. Here we reported that H. variegata adults were attracted by the crude honeydew of A. gossypii, and we identified fifteen volatiles using headspace solid-phase microextraction gas chromatography/mass spectrometry (SPME-GC/MS). Electroantennogram (EAG) results showed that H. variegata exhibits a significant dose-dependent response to nine volatiles from honeydew. Y-tube olfactometer and cage predation tests showed that 1-heptanol, 2-ethyl-1-hexanol, 2-phenylethanol, and 2-methyl-1-propanol attracted H. variegata adults. Furthermore, our study also elucidated the relationship between honeydew compounds and microorganisms. The findings demonstrated that the compounds 2-ethyl-1-hexanol, 2-phenylethanol, and 2-methyl-1-propanol originate from five distinct cultivable bacteria identified using the 16S rRNA markers. Our results provide potential eco-friendly strategies for enhancing biological control of aphids.